Apolipoprotein E2 (Arg136 → Cys) mutation in the receptor binding domain of apoE is not associated with dominant type III hyperlipoproteinemia1 - März, Winfried; Hoffmann, Michael Marcus; Scharnagl, Hubert; Fisher, Eva; Chen, Minchun; Nauck, Markus; Feussner, Giso; Wieland, Heinrich (Journal of lipid research, 1998)
Using apoE phenotyping by immunoblotting and apoE genotyping we identified four heterozygous carriers of a rare apolipoprotein (apo) E2 variant, apoE2 (Arg136 → Cys). ApoE2 (Arg136 → Cys) was not distinct from apoE2 (Arg158 → Cys) by phenotyping, but produced a unique pattern of bands on CfoI restriction typing of a 244 bp apoE gene fragment. Two of the four apoE2 (Arg136 → Cys)/3 heterozygotes had elevated triglycerides, two were normolipidemic. The composition of very low density lipoproteins (VLDL) was normal in each of the four apoE2 (Arg136 → Cys) carriers, regardless of the triglyceride concentrations. None of the apoE2 (Arg136 → Cys) carriers displayed a broad β-band and none revealed β-migrating particles in the VLDL. The two hypertriglyceridemic carriers of apoE2 (Arg136 → Cys) were, therefore, classified as having type IV rather than type III hyperlipoproteinemia. LDL receptor binding activities were studied using recombinant apoE loaded to dimyristoylphosphatidylcholine (DMPC) vesicles and to VLDL and from an apoE-deficient individual. LDL receptor binding of apoE2 (Arg136 → Cys) was 14% of apoE3 and was thus higher than that of apoE2 (Arg158 → Cys). Both apoE2 (Arg136 → Cys) and apoE2 (Arg158 → Cys) displayed substantial heparin binding (61 and 53% of apoE3, respectively). As the dominant apoE variants known so far are characterized by more pronounced reductions of heparin binding, we suggest that apoE2 (Arg136 → Cys) is not associated with dominant expression of type III hyperlipoproteinemia. These findings lend support to the concept that apoE variants predisposing to dominant type III hyperlipoproteinemia differ from recessive mutations by a more severe defect in heparin binding.—März, W., M. M. Hoffmann, H. Scharnagl, E. Fisher, M. Chen, M. Nauck, G. Feussner, and H. Wieland. Apolipoprotein E2 (Arg136 → Cys) mutation in the receptor binding domain of apoE is not associated with dominant type III hyperlipoproteinemia.